MiRNA-based strategy for modulation of influenza A virus infection. (11th June 2018) - Keshavarz, Mohsen; Dianat-Moghadam, Hassan; Sofiani, Vahideh Hamidi; Karimzadeh, Mohammad; Zargar, Mohsen; Moghoofei, Mohsen; Biglari, Hamed; Ghorbani, Saied; Nahand, Javid Sadri; Mirzaei, Hamed
Influenza A virus is known worldwide as a threat associated with human and livestock diseases. Hence, identification of physiological and molecular aspects of influenza A could contribute to better design of therapeutic approaches for reducing adverse effects associated with disease caused by this virus. miRNAs are epigenetic regulators playing important roles in many pathological processes that help in progression of influenza A. Besides miRNAs, exosomes have ememrged as other effective players in influenza A pathogenesis. Exosomes exert their effects via targeting their cargos (e.g., DNAs, mRNA, miRNAs and proteins) to recipient cells. Here, we summarized various roles of miRNAs and exosomes in influenza A pathogenesis. Moreover, we highlighted therapeutic applications of miRNAs and exosomes in influenza.